Implementation of a combined bioinformatics and experimental approach to address lncRNA mechanism of action: The example of NRIR - Mariotti, Barbara; Di Blas, Costanza; Bazzoni, Flavia (Frontiers in Molecular Biosciences, 2022)
In this study, we demonstrate the benefit of applying combined strategies to analyze lncRNA action based on bioinformatics and experimental information. This strategy was developed to identify the molecular function of Negative Regulator of Interferon Response (NRIR), a type I interferon-stimulated gene (ISG), that we have previously demonstrated to be involved in the upregulation of a subset of ISGs in LPS-stimulated human monocytes. In this study, we provide experimental evidence that NRIR is localized in cellular nuclei, enriched on the chromatin fraction, and upregulates ISGs acting at transcriptional level. In silico analysis of secondary structure identified distinct NRIR structural domains, comprising putative DNA- and protein-binding regions. In parallel, the presence of a putative DNA-binding domain in NRIR and of five putative NRIR-binding sites in the promoter of NRIR-target genes support the function of NRIR as a transcriptional regulator of its target genes. By the use of integrated experimental/bioinformatics approaches, comprising database and literature mining together with in silico analysis of putative NRIR-binding proteins, we identified a list of eight transcription factors (TFs) shared by the majority of NRIR-target genes and simultaneously able to bind TF binding sites enriched in the NRIR-target gene promoters. Among these TFs, the predicted NRIR:STAT interactions was experimentally validated by RIP assay.